2013
DOI: 10.1097/shk.0b013e3182a6953e
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Renin-AngioteNsin System Contributes to acute Lung Injury Caused by Hind-limb Ischemia-Reperfusion in Mice

Abstract: The mechanism of acute lung injury (ALI) following limb ischemia-reperfusion (LIR) is not yet clear. We speculate that the unbalanced expression of angiotensin-converting enzymes (ACE and ACE2) and angiotensins [Ang II and Ang-(1-7)] in the renin-angiotensin system (RAS) is a major cause of ALI. To prove this hypothesis, pathological changes, lung edema, and permeability of wild-type mice at different time points within 12 h of reperfusion after 2 h of hind-limb ischemia were first detected by morphological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…24 This cellular dysfunction and disintegrity might play a role in the etiopathology of remote organ damage including liver, kidney and lung in lower limb ischemia-reperfusion injury. [3][4][5]16 The kidneys are particularly involved in the remote alteration phenomenon following skeletal muscle ischemia-reperfusion injuries. 23 Although a diversity of mechanisms exist, oxidative stress, inflammatory response, and the apoptosis are believed to be the primary causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 This cellular dysfunction and disintegrity might play a role in the etiopathology of remote organ damage including liver, kidney and lung in lower limb ischemia-reperfusion injury. [3][4][5]16 The kidneys are particularly involved in the remote alteration phenomenon following skeletal muscle ischemia-reperfusion injuries. 23 Although a diversity of mechanisms exist, oxidative stress, inflammatory response, and the apoptosis are believed to be the primary causes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several animal studies showed that hind limb I/R injury affected several organs, including the kidneys, liver and lungs. [3][4][5] The highly selective and potent a2-adrenergic agonist dexmedetomidine (DXM) is an effective sedative, anxiolytic, and analgesic agent 6 with protective effects against I/R injury in several organs, including the heart, 7 brain, 8 and kidneys, 9 probably due to the antioxidant and anti-inflammatory properties of the compound. [10][11][12] Curcumin (CUR) has a long history of therapeutic use in Indian and Chinese medicine and has several pharmacological properties, including antioxidant, anti-inflammatory, antiviral, antimicrobial, antifungal, as well as anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…RAS, which is vital in the regulation of blood pressure, electrolytes, and total body volume, is closely related to lung injury [7]. Studies have shown that Ang II as an important component of RAS is involved in the pathogenesis of lung injury in different models, and most actions of Ang II are related to the AT1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…RAS is thought to be a systemic cascade and plays an important role in fluid balance and blood pressure regulation [5]. However, many studies support the pivotal role of tissue specific RAS in injury and repair [6][7][8][9][10][11]. A subset of these studies supports the existence of an intrinsic angiotensin system in lung alveolar epithelial cells (AECs) and demonstrates that activation of this local angiotensin system plays a major role in lung injury [12].…”
Section: Introductionmentioning
confidence: 99%